Stable DNA Sequence Over Close-Ending and Pairing Sequences Constraint - Li, Xue; Wei, Ziqi; Wang, Bin; Song, Tao (Frontiers in Genetics, 2021)
DNA computing is a new method based on molecular biotechnology to solve complex problems. The design of DNA sequences is a multi-objective optimization problem in DNA computing, whose objective is to obtain optimized sequences that satisfy multiple constraints to improve the quality of the sequences. However, the previous optimized DNA sequences reacted with each other, which reduced the number of DNA sequences that could be used for molecular hybridization in the solution and thus reduced the accuracy of DNA computing. In addition, a DNA sequence and its complement follow the principle of complementary pairing, and the sequence of base GC at both ends is more stable. To optimize the above problems, the constraints of Close-ending and Pairing Sequences Constraint (PSC) along with the Improved Chaos Whale (ICW) optimization algorithm were proposed to construct a DNA sequence set that satisfies the combination of constraints. The ICW optimization algorithm is added to a new predator–prey strategy and sine and cosine functions under the action of chaos. Compared with other algorithms, among the 23 benchmark functions, the new algorithm obtained the minimum value for one-third of the functions and two-thirds of the current minimum value. In terms of the Wilcoxon rank-sum test results, more than half of them had advantageous values. The DNA sequences satisfying the constraint combination obtained the minimum of multiple fitness values and had stable and usable structures.